The Influence of Railway Station on Residential Property Values-Spatial Hedonic Approach The Case of Serpong’s Railway Station - Ibnu Syabri (Institut Teknologi Bandung, 2011)
Abstract. Urban area management in developed countries such as the United States and Japan which have implemented “Transit Oriented Development” (TOD), shows that TOD seems capable of increasing the property values and and reducing household expenditure for transportation costs. However, applying the TOD concept in Indonesian cities such as Jakarta, Surabaya, and Medan, is a unique and considerable challenge, considering urban transportation condition in Indonesia that is far different from the conditions in urban areas in developed countries. One of important infrastructure policy issues for Jakarta and other rapidly growing cities in Indonesia is how to raise fiscal revenues through “value capture”, in which the increase the property values is due to better access and services from the existances of the railway stations. The research is based on a case study in Serpong, a neighborhood in Jakarta Metropolitan Area (JMA), Indonesia. The focus of this study is to test the basic viewpoint of TOD strategy which is how transport infrastructure such as railway stations influence the property values of a neighborhood. Following Anselin and Lozano-Gracia’s (2009) framework, this paper uses a spatial hedonic pricing model that allows to measure both “direct and in-direct effects” or “externality spillovers” from the existence of the railway stations. Abstrak. Pengelolaan kawasan perkotaan di negara-negara maju seperti Amerika Serikat, Jepang, dan lain-lain yang telah menerapkan konsep